2016
DOI: 10.1080/00140139.2016.1229042
|View full text |Cite
|
Sign up to set email alerts
|

Pressure thresholds and stiffness on the plantar surface of the human foot

Abstract: The objective was to develop a methodology to assess Pressure Discomfort Thresholds (PDT), Pressure Pain Thresholds (PPT), and tissue stiffness on the plantar surface of the foot. Ten male and ten female participants volunteered for the study. Foot landmarks were used to create a standardized grid-type template of 95 points. For each test point, PPT and PDT values were obtained, and stiffness was calculated for each of the twenty participants. Cluster analyses were performed to determine the regions of similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Pressure pain threshold was measured with algometer (Pain Test FPX 25) using 1-cm² rubber tip on the middle of anatomical site of enthesis zone of plantar fascia to the heel. 10 , 11 Pressure was applied slowly until the participant first felt the pain and responded by saying “stop.” In each heel, there were three measurements taken with 30 seconds break after each measurement. The average of all three measurements in each heel was recorded as a final value.…”
Section: Methodsmentioning
confidence: 99%
“…Pressure pain threshold was measured with algometer (Pain Test FPX 25) using 1-cm² rubber tip on the middle of anatomical site of enthesis zone of plantar fascia to the heel. 10 , 11 Pressure was applied slowly until the participant first felt the pain and responded by saying “stop.” In each heel, there were three measurements taken with 30 seconds break after each measurement. The average of all three measurements in each heel was recorded as a final value.…”
Section: Methodsmentioning
confidence: 99%
“…The finding of a lower pain threshold in young women than in young men ( Figure 3 , Figure 4 , Figure 5 and Figure 6 ) also agrees with the literature data [ 9 , 24 , 25 ]. Several studies reported that men have significantly higher pressure pain thresholds than women [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a very low pain tolerance for young women and/or high sensitivity of skin nociceptors to mechanical stimuli, leading to greatly increased activity over a small variation of pressure; these hypotheses deserve further study. Moreover, it is possible that women express pain while men holdback emotions of pain [ 1 ]. This aspect represents an important limitation of this experimental model that is based on the personal identification of pain intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations